The relationship of social entrepreneurship orientation and the halal logistics values creation on food and beverage MSME’S in Malaysia - Hasrul, Hashom (2023)
The food and beverage industry, particularly the Micro, Small, and Medium Enterprises (MSMEs), continues to serve as a vital contributor to the overall economic growth of both the local community and the country. However, there is a lack of comprehensive research on MSME entrepreneurs and their impact on the social sector. This study has been conducted to identify factors contributing to social entrepreneurship and improving firm performance. Additionally, the study evaluates the value creation of halal logistics, which includes packaging, warehousing, transportation, and halal management systems. Therefore, the study examines the relationship between the independent variable factors of Social Entrepreneurship Orientation and the dependent variable of Firm Performance. This study also examines the influence of the moderating variables of Halal Logistics Value Creation on the relationship between Social Entrepreneurship Orientation and Firm Performance. This study is conducted using an online questionnaire data collection strategy based on simple random probability sampling. The study involved 248 samples among MSMEs throughout Malaysia. The study found that the relationship between Social Entrepreneurial Orientation, innovativeness, and socialness has a significant positive relationship with Firm Performance. The findings of the study also discovered that the variable factor of halal management system simplification significantly affects the relationship between the variable factor of Social Entrepreneurship Orientation, innovativeness, and socialness with Firm Performance. In addition, the social entrepreneurship orientation variable and the Halal Logistics Values Creation variable have a significant relationship with Firm Performance as unidimensional variables. In conclusion, this study contributes to findings that show the tendency of top management/MSME owners in Malaysia towards Social Entrepreneurship Orientation and Halal Logistics Values Creation.